Changes in the levels of some cytokines when using blood purification in COVID-19 patients - Yu. S. Polushin; R. V. Аkmalova; D. V. Sokolov; I. V. Bovkun; E. G. Gavrilova; I. V. Shlyk; E. V. Parshin; S V. Lapin; O. Yu. Tkachenko (Вестник анестезиологии и реаниматологии, 2021)
The use of high-adsorption membrane hemofiltration in COVID-19 positive patients to reduce the severity of a cytokine storm is clearly beneficial but at the same time, there are no certain procedures for its practical use.The objective: to study the change in the levels of IL-6 and IL-18 in response to prolonged (24-72 hours) high-adsorption membrane hemofiltration.Subjects and methods. We retrospectively analyzed the data on IL-6 and IL-18 levels and their changes in 69 patients who were COVID-19 positive and had different degrees of lung damage, they had received high-adsorption membrane hemofiltration during their stay at the intensive care unit. The extent of lung lesions was the following: 4 people had CT-2, 44 people had CT-3, and 21 patients had CT-4. 18 patients had an unfavorable outcome of the disease. High-adsorption membrane hemofiltration (Prismaflex) was used in the group of patients who had clinical signs of the rapid progression of the disease and also such laboratory findings as elevated values of C-reactive protein (above 100 mg/L), ferritin (more than 600 μg/L), and progression of lymphopenia. This intervention lasted for 24 hours at CT-2/3, and 48 hours at CT-4. The effluent dose was 30.0 ± 6.4 ml/kg/h. The levels of IL-6, IL-18, and procalcitonin were tested before and after the completion of the intervention, and the difference between their concentration before and after high-adsorption membrane hemofiltration was calculated. The potential association between received data (IL-6, IL-18, delta of IL-6, delta of IL-18) and degree of lung damage and outcomes was analyzed.Results. It was detected that the more the lungs were affected, the lower levels of IL-6 and IL-18 were and vice versa and this correlation was not associated with the use of tocilizumab (used in 44 people). The maximum decrease in the level of cytokines was observed in the group of patients with CT-2. There was a significant association between the delta of IL-6 (F = 6.69; p ≤ 0.05) and the outcome which was especially pronounced in people with a favorable outcome.Conclusion. As the inflammation progresses in the lungs, the levels of IL-6 and IL-18 decrease which may be a manifestation of the depletion of the cytokine storm. The use of prolonged high-adsorption membrane hemofiltration (24-48 h) allows reducing the level of cytokines. The delta value reflects a decrease in IL-6 concentration, it significantly correlates with the outcome which indicates the importance of using this method in a continuous mode.